Qualitative Phenomenological Study: Understanding the Experience of Adolescents’ Mental Health Problems in Urban Areas - Riris Diana Rachmayanti; Andrei Ramani; Nur Farida Kusumawati; Yulia Wardita; Ayu Citra Mayasari; Anysiah Elly Yulianti; Dani Nasirul Haqi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Adolescence is referred to as a period of